2005
DOI: 10.1097/01.bpo.0000162015.44865.5e
|View full text |Cite
|
Sign up to set email alerts
|

Results of an Accelerated Ponseti Protocol for Clubfoot

Abstract: The Ponseti method has demonstrated excellent results when performed at weekly intervals, but it is not known whether correction can be accomplished in a shorter amount of time. This study evaluated the success in correction in relation to time between casts (5 or 7 days). The authors retrospectively reviewed 230 patients (319 clubfeet). One hundred sixty-five patients (72%) had undergone previous nonsurgical treatment elsewhere. Patients were assigned to 5 or 7 days based solely on geography. Ninety percent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
151
1
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(171 citation statements)
references
References 36 publications
9
151
1
10
Order By: Relevance
“…In another study by Laaveg et al [8], the average duration was 8.6 weeks. Morcuende et al [9] reported an average time from the first cast to tenotomy as 16 days for one group and 24 days for another group in the same study. Their study showed that the duration of plaster casts can be decreased by using the accelerated Ponseti protocol for clubfoot treatment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In another study by Laaveg et al [8], the average duration was 8.6 weeks. Morcuende et al [9] reported an average time from the first cast to tenotomy as 16 days for one group and 24 days for another group in the same study. Their study showed that the duration of plaster casts can be decreased by using the accelerated Ponseti protocol for clubfoot treatment.…”
Section: Discussionmentioning
confidence: 97%
“…In another study by Laaveg et al [8], the mean number of casts during their treatment was seven. Morcuende [9,10] reported that 90% of the patients required five or fewer casts. Over a period of time, with more experience, people have started changing plaster casts at shorter intervals [9] and fewer casts per feet give faster results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though Ponseti advocates the use of plaster for the cast material as it is easier to mold, there are reports on the successful use of fiberglass materials for achieving clubfoot correction [15,53]. Regardless of the casting material used, the casts are changed every 5 to 7 days [48]. As the Ponseti method has spread around the world there is increasing experience and success with the use of this method in children older than 1 year of age with neglected clubfoot [22,45,61,64].…”
Section: Ponseti Methodsmentioning
confidence: 99%
“…When needed, surgery was performed by orthopaedic residents supervised by the attending staff. Although patients who could travel to and from the hospital were treated as outpatients (cast changes every 7 days), those coming from more remote regions were admitted to our rehabilitation unit for an ''accelerated'' Ponseti protocol (cast changes every 5 days) [18]. The majority of patients treated using the Ponseti method require surgery for residual equinus after a plateau is reached in casting, typically a percutaneous tendo-Achilles release (HCR).…”
Section: Methodsmentioning
confidence: 99%